BUILDING LEARNING WITH A REALISTIC MATHEMATICS EDUCATION APPROACH - Nursupiamin; Dwi Risky Arifanti (International Journal of Teaching and Learning, 2024)
The realistic mathematics approach is one of the approaches to learning mathematics that was developed to bring mathematics closer to students. Real problems from everyday life are used as a starting point for learning mathematics to show that mathematics is actually close to everyday life. A main principle of Realistic Mathematics Education is that students must participate actively in the learning process. Learners must be given the opportunity to build their own knowledge and understanding. Abstract mathematical concepts need to be transformed into things that are real for students. Realistic problems given to students do not always have to use problems that exist in the students' real world or can be found in students' daily lives. A problem is called realistic if the problem given can be imagined or real in the students' minds. Applying a realistic mathematical approach will change learning to be easy for students to understand. This approach develops children's thinking patterns by finding their own concepts in mathematics through establishing relationships between the material and children's daily lives. So that the mathematical concepts learned can be applied in life. From this, children's mathematical understanding will increase.